Pulmonary Tuberculosis Disease Among Immigrant Detainees: Rapid Disease Detection, High Prevalence of Asymptomatic Disease, and Implications for Tuberculosis Prevention. (16th April 2020) - Boardman, Nicole J; Moore, Tiffany; Freiman, Jennifer; Tagliaferri, Geri; McMurray, Dakota; Elson, Diana; Lederman, Edith
Abstract: Background: Rapid screening for tuberculosis (TB) disease at intake into immigrant detention facilities allows for early detection and treatment. Detention facilities with United States Immigration and Customs Enforcement (ICE) Health Service Corps (IHSC) medical staffing utilize chest radiography and symptom screening as the primary screening for pulmonary TB (PTB) disease. This analysis describes the demographic, clinical, and microbiological characteristics of individuals identified with TB disease at these facilities. Methods: We conducted a retrospective analysis to describe the population of immigrant detainees identified via chest radiography with PTB disease between 1 January 2014 and 31 December 2016 at facilities with IHSC medical staffing. We collected demographic variables, clinical presentation, diagnostic testing results, and microbiological findings. We generated descriptive statistics and examined univariate and multivariate associations between the variables collected and symptomatic status. Results: We identified 327 patients with confirmed PTB disease (incidence rate, 92.8 per 100 000); the majority of patients were asymptomatic (79.2%) at diagnosis. Adjusting for all other variables in the model, the presence of cavitary lesions, acid-fast bacillus smear positivity, and multilobar presentation were significantly associated with symptomatic status. Among all patients identified with TB disease who had a tuberculin skin test (TST) result recorded, 27.2% were both asymptomatic and TST negative, including those with smear-positive disease. Conclusions: Asymptomatic PTB disease is a significant clinical entity among immigrant detainees and placement in a congregate setting calls for aggressive screening to prevent transmission. Early identification, isolation, and treatment of TB disease benefit not only the health of the patient, but also the surrounding community. Abstract : Nearly 80% of detainees with tuberculosis disease identified via radiographic screening were asymptomatic, suggesting that radiographic screening identifies tuberculosis earlier in the disease process. Among patients with a tuberculin skin test (TST) recorded, 27.2% were asymptomatic and TST-negative, including patients with smear-positive and cavitary disease.